The input-output table for the Alentejo region in Portugal - Belbute, José (2013)
Portugal is a not a homogenous territory even though it is a small country. Each region has different characteristics, which makes the country as an evident case for the need of an effective cohesion policy leading to a diminishment of regional disparities. This paper presents a preliminary version of the input-output table for Alentejo, a Portuguese region through the regionalization of the input-output national table, for the year 2008. As it is well known the input-output (IO) model is particularly appropriate for the analysis of the effects of demand on supply (possibly in territorial/regional terms). As such, from the descriptive point of view, the IO model is useful for the analysis of explanatory factors of (regional) growth. Moreover, from a decision-making point of view it allows to support (regional) policy making in order to change (in the most favorable possible way) the (regional) production structure. This is particularly important for the fragile region of Alentejo, while the largest one, where such instruments are scarce. Furthermore, the second quadrant, from which demand effects can be considered and extended to third quadrant, where a proper quantification of inter-regional imports is to be considered, complete the table. From the production perspective, our preliminary results suggest weak inter- sectors relations in the Alentejo region making it susceptible to lose a substantial part of the potential effects, which may spillover to other Portuguese regions. In particular, more than 75% of the indirect effects are below 0.05. Furthermore, tobacco, food, beverages, crude refineries, fishing & aquaculture, clothing and agriculture sectors have the most relevant type II multipliers. However, only clothing and beverages have higher aggregate indirect effects over all other industries as a result of an increase of one euro on their final demands. Regarding type I multipliers, our results suggests a different picture. Forestry, tobacco, leather, beverages, among other have important direct and indirect effect. These results have important policy implications in this fragile region. There is, however, another possible use of the model, based on the determination of how to alter the production structure, in order to potentiate the effect of drag of all sectors of production, which may have great potential for development of strategies for economic policy.